Táxons superiores são suficientes para representar padrões de biodiversidade - Oliveira Junior, Sandro Souza de (2019)
The paucity of knowledge about biodiversity (Linnean Shortfall) and about the geographic distributions of many species (Wallacean Shortfall) makes it difficult to conduct studies that seek to explain biodiversity patterns. One way to overcome this difficulty consists in the utilization of data with lower taxonomic resolution, an approach called taxonomic sufficiency. The main aim of this study was to evaluate, through a systematic review and meta-analysis, whether this approach is reliable. We also evaluated whether the strength of the taxonomic sufficiency (i.e. the relationship between datasets at high a low taxonomic resolutions) depended on different factors, including taxonomic level (genus, family, order and class), ecosystem type (aquatic and terrestrial), biological group (e.g. invertebrates, vertebrates and plants), spatial extent and higher taxon to species richness ratio. We found that the taxonomic sufficiency was a reliable approach in revealing species richness and compositional patterns, independently of biological groups and ecosystem types. As expected, the strength of the taxonomic sufficiency decreased as the taxonomic resolution decreased. In addition, the ratio between the richness of lower and higher taxonomic levels (φ) is a strong indicator of the taxonomic sufficiency, whereas the spatial scale was not influential. Therefore, the use of higher taxa (e.g. genera) is a reliable approach to save time and resources in biomonitoring programs and differs in this regard from other approaches already evaluated in the scientific literature (e.g. biological surrogacy).